Supply Chain Financing as an Antecedent of Supply Chain Success: An Indonesian Perspective - Juniati, Sri; Iskandar, Asep Deni; Rosita, Ai; Alaeddin, Omar (ExcelingTech, 2019)
The prime objective of this empirical research is exploring the role of supply chain financing in enhancing the supply chain management performance of the firms operating in the manufacturing sector of Indonesia. In addition to that the current study has also intended to study the impact of firm cash flow on supply chain management performance. Finally, the study has also examined the mediating role of firm cash flow in the relationship between supply chain financing and supply chain management performance. The multiple regression is used to achieve the novel objectives of the current study. The data by means of an adapted questionnaire is collected form the finance and operation managers of manufacturing firms listed in Indonesian stock exchange. Prior to regression analysis the data has undergone basic diagnostic test and after confirmation of reliability, validity and multicollinearity we have carried out a regression analysis. The direct relations of hypotheses H1,H2,and H3 are significant and positive, whereas the results of H4 are also significant, Which indicates that the firms cash flow mediates the relationship between supply chain financing and supply chain management performance